1999
DOI: 10.1017/s0021963098003370
|View full text |Cite
|
Sign up to set email alerts
|

Can Autism Be Diagnosed Accurately in Children Under 3 Years?

Abstract: This study investigated the reliability and stability of an autism diagnosis in children under 3 years of age who received independent diagnostic evaluations from two clinicians during two consecutive yearly evaluations. Strong evidence for the reliability and stability of the diagnosis was obtained. Diagnostic agreement between clinicians was higher for the broader discrimination of autism spectrum vs. no autism spectrum than for the more specific discrimination of autism vs. PDD-NOS. The diagnosis of autism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
132
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(146 citation statements)
references
References 7 publications
11
132
1
2
Order By: Relevance
“…Research attempting to differentiate autism and Asperger's disorder suggests these subgroups differ only in symptom severity or IQ Myhr 1998;Ozonoff et al 2000), indicating they are not separate disorders. Further, diagnostic agreement for autism spectrum disorder is excellent, whereas agreement for the DSM-IV pervasive developmental disorder subtypes is far lower (Mahoney et al 1998;Stone et al 1999;Volkmar et al 1994). Many clinicians and researchers now concur that autism is a spectrum disorder and that Asperger's disorder is not a separate and distinct disorder, but is at the high functioning or mild end of the autism continuum (Eisenmajer et al 1996;Frith 2004;Macintosh and Dissanayake 2004;Manjiviona and Prior 1995;Mayes and Calhoun 2003;Mayes et al 2001;Miller and Ozonoff 2000;Myhr 1998;Ozonoff et al 2000;Prior et al 1998;Schopler 1996Schopler , 1998Wing 1998).…”
Section: Checklist For Autism Spectrum Disordermentioning
confidence: 99%
“…Research attempting to differentiate autism and Asperger's disorder suggests these subgroups differ only in symptom severity or IQ Myhr 1998;Ozonoff et al 2000), indicating they are not separate disorders. Further, diagnostic agreement for autism spectrum disorder is excellent, whereas agreement for the DSM-IV pervasive developmental disorder subtypes is far lower (Mahoney et al 1998;Stone et al 1999;Volkmar et al 1994). Many clinicians and researchers now concur that autism is a spectrum disorder and that Asperger's disorder is not a separate and distinct disorder, but is at the high functioning or mild end of the autism continuum (Eisenmajer et al 1996;Frith 2004;Macintosh and Dissanayake 2004;Manjiviona and Prior 1995;Mayes and Calhoun 2003;Mayes et al 2001;Miller and Ozonoff 2000;Myhr 1998;Ozonoff et al 2000;Prior et al 1998;Schopler 1996Schopler , 1998Wing 1998).…”
Section: Checklist For Autism Spectrum Disordermentioning
confidence: 99%
“…Collectively, these studies found AD to be the most stable diagnosis and PDD-NOS, the least stable (Cederlund et al 2008;Charman et al 2005;Chawarska et al 2007;Kleinman et al 2008;Moss et al 2008;Turner and Stone 2007; van Daalen et al 2009). Diagnostic stability has also been linked to age of initial evaluation, cognition and language ability, and participation in early intervention (Itzchak and Zachor 2009;Stone et al 1999;Turner and Stone 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the age for earliest reliable diagnosis was thought to be between 4 and 5 years (Howlin and Ashgarian 1999). However, a number of recent studies have shown that ASD can be accurately detected in children under the age of 3 years (Charman and Baird 2002;Cox et al 1999;Eaves and Ho 2004;Lord 1995;Moore and Goodson 2003;Stone et al 1999). Such studies have focused on: (1) stability of very early diagnosis, (2) applicability of specific instruments to very young children, and (3) whether DSM-IV symptoms (American Psychiatric Association 1994) apply to very young children.…”
Section: Introductionmentioning
confidence: 99%
“…One major criticism of using the ADI-R to diagnose toddler age children is that it only diagnoses Autistic Disorder, and not PDD-NOS. Since to show Autistic Disorder, a child must show deficits in all three areas (socialization, communication, and stereotyped/ repetitive behaviors), and many young children only show problems in the first two areas, using the ADI-R may fail to diagnose such children with an ASD (Charman and Baird 2002;Cox et al 1999;Ventola et al 2006;Lord 1995;Stone et al 1999). Conversely, many children with severe global developmental delay meet diagnostic criteria for autism on this measure because they are engaging in a number of repetitive mannerisms, even at a very young age (Lord 1995).…”
Section: Introductionmentioning
confidence: 99%